Bermain Peran (Role Play) dan Peningkatan Keterampilan Sosial Anak Usia Dini - Alhamdu Alhamdu Alhamdu; Chintia Viranda; Listya Istiningtyas (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2019)
This research intends to find out whether there is an influence in played a role play on social skills at early-aged children. The type of research used Quasi Experimental design with Time Series Design. The sample in this research amounted to 8 students with a purposive sampling technique. The research instrument used was ceklist observation, a teacher questionnaire, and parents questionnaire based on aspects of social skills according to Jarolimek (1993) which was analyzed by Paired Sample t test with the help of the program SPSS versi 22 for windows. The results of the study get significance value (2-tailed) (0,000) <α (0,05). Which means that Ho is rejected and Ha is accerpted, so it can be cocluded that treatment of role playing in this study influential in improving on social skills at early-aged children.Keywords : Role Play, Social Skills, Early-aged Children